Exploring hyperhidrosis and related thermoregulatory symptoms as a possible clinical identifier for the dysautonomic subtype of Parkinson’s disease - Daniel J. van Wamelen; Valentina Leta; Aleksandra M. Podlewska; Yi-Min Wan; Katarina Krbot; Elina Jaakkola; Pablo Martinez-Martin; Alexandra Rizos; Miriam Parry; Vinod Metta; Kallol Ray Chaudhuri (Dr. Dietrich Steinkopff Verlag GmbH and Co. KG, 2022)
Objective
To identify associated (non-)motor profiles of Parkinson’s disease (PD) patients with hyperhidrosis as a dominant problem.
Methods
This is a cross-sectional, exploratory, analysis of participants enrolled in the Non-motor Longitudinal International Study (NILS; UKCRN No: 10084) at the Parkinson’s Centre at King’s College Hospital (London, UK). Hyperhidrosis scores (yes/no) on question 28 of the Non-Motor Symptom Questionnaire were used to classify patients with normal sweat function (n = 172) and excessive sweating (n = 56) (Analysis 1; n = 228). NMS scale (NMSS) question 30 scores were used to stratify participants based on hyperhidrosis severity (Analysis 2; n = 352) using an arbitrary severity grading: absent score 0 (n = 267), mild 1–4 (n = 49), moderate 5–8 (n = 17), and severe 9–12 (n = 19). NMS burden, as well as PD sleep scale (PDSS) scores were then analysed along with other correlates.
Results
No differences were observed in baseline demographics between groups in either analysis. Patients with hyperhidrosis exhibited significantly higher total NMSS burden compared to those without (p < 0.001). Secondary analyses revealed higher dyskinesia scores, worse quality of life and PDSS scores, and higher anxiety and depression levels in hyperhidrosis patients (p < 0.001). Tertiary analyses revealed higher NMSS item scores for fatigue, sleep initiation, restless legs, urinary urgency, and unexplained pain (p < 0.001).
Conclusions
Chronic hyperhidrosis appears to be associated with a dysautonomia dominant subtype in PD patients, which is also associated with sleep disorders and a higher rate of dyskinesia (fluctuation-related hyperhidrosis). These data should prompt the concept of hyperhidrosis being used as a simple clinical screening tool to identify PD patients with autonomic symptoms.